Smarter Than Thou, Holier Than Thou: The Dynamic Interplay Between Cognitive and Moral Enhancement - Pavarini, Gabriela; McKeown, Alex; Singh, Ilina (Frontiers in Pharmacology, 2018)
The debate about the desirability of using drugs to enhance human skills encompasses cognitive abilities such as memory and attention, and moral capacities such as emotional empathy and a sense of fairness. These two strands of literature in bioethics have grown relatively independent from each other, and an implicit framing assumption has emerged suggesting that apparently ‘value-free’ cognitive capacities and paradigmatically moral capacities are distinct and vary independently of each other. Here we identify key distinctions between competing accounts of cognitive enhancement and moral enhancement and argue that, despite the polarised nature of the bioethical debate, cognitive and moral capacities are intertwined. For example, moral behaviour can be improved by enhancing so-called ‘value-free’ abilities such as attention span; and cognitive skills can be honed by means of socio-moral interaction. Further, cognitive skill is frequently assigned the abstract status of virtue and treated in the same way as more paradigmatically ‘moral’ traits. We argue that the distinction between moral and cognitive enhancement is more apparent than real, since despite being nominally treated as distinct, cognitive and moral skills overlap significantly and are frequently interdependent. As such we present evidence to support the claim that the enhancement of these two kinds of capacities cannot be clearly disaggregated from each other in the way that the theoretical poles of the debate in the literature suggest. We synthesise relevant scientific and bioethical literature and combine it with a line of analysis derived from Peter Hacker and others to show how a linguistically-informed approach can show us more clearly the terms of what can be said intelligibly about cognitive and moral skills and their enhancement. As a result of this analysis we conclude that ethical questions in human bioenhancement should be considered in terms of flourishing at the level of the whole person imbued with feelings, thoughts, intentions and abilities and embedded within a particular social context, rather than the pharmacological modulation of particular cognitive or affective capacities which, though conceptually discrete, in the embodied context of moral agency are profoundly intertwined.